What Drives Stock Price Movements? - Chen, Long; Da, Zhi; Zhao, Xinlei (Review of Financial Studies, 2013)
[A central issue in finance is whether stock prices move because of revisions in expected cash flows or discount rates, and by how much of each. Using direct cash flow forecasts, we show that stock returns have a significant cash flow news component whose importance increases with the investment horizon. For horizons over two years, cash flow news is more important. These conclusions hold at both the firm and aggregate levels, and diversification plays a secondary role in affecting the relative importance of cash flow and discount rate news. Our findings highlight the importance of cash flows in asset pricing.]